Predictors of thromboxane levels in patients with non-ST-elevation acute coronary syndromes on chronic aspirin therapy - Niccoli, Giampaolo; Giubilato, Simona; Leo, Andrea; Cosentino, Nicola; Fracassi, Francesco; Cataneo, Leonardo; Porto, Italo; Leone, Antonio Maria; Burzotta, Francesco; Trani, Carlo; Biasucci, Luigi Marzio; Narducci, Maria Lucia; Pulcinelli, Fabio Maria; Crea, Filippo (Thrombosis and Haemostasis, 2012)
High levels of thromboxane A2 (TxA2), a key mediator of platelet activation and aggregation, are associated with an increased risk of cardiovascular events. We aimed at assessing the predictors of higher plasma levels of TxB2, the stable metabolite of TxA2, in consecutive patients presenting with non-ST-elevation acute coronary syndrome (NSTE-ACS) on previous aspirin (ASA) treatment undergoing coronary angiography. Ninety-eight consecutive patients (age 61 ± 11, 75% males) with NSTE-ACS, on previous chronic ASA treatment, were prospectively enrolled in this study. Coronary disease extent was assessed by angiography according to the Bogaty score. In all patients, admission plasma levels of TxB2 (pg/ml) were measured by enzyme-linked immunosorbent assay, and patients showing TxB2 levels in the fourth quartile were compared to patients showing TxB2 levels in the lower quartiles. Multivariable logistic regression analysis showed that platelet count (odds ratio [OR] 1.18, 95% confidence interval [CI] 1.02–1.63, p=0.04), multivessel coronary disease (OR 1.37, 95% CI 1.13–3.67, p=0.03), and coronary atherosclerosis extent index (OR 1.91, 95% CI 1.45–6.79, p=0.001) were independent predictors of TxB2 level upper quartile. Of note, C-reactive protein serum levels were similar in patients with TxB2 levels in the upper quartile as compared to those in the lower quartiles (p=0.49). In conclusion, NSTE-ACS patients with severe coronary atherosclerosis may have incomplete suppression of TxA2 production despite chronic ASA therapy. This finding suggests that additional efforts should be made to lower TxA2 levels in patients with widespread coronary artery disease.
Keywords: Thromboxane A2; aspirin; coronary atherosclerosis; non-ST-elevation acute coronary syndromes